HER2 and ß-catenin protein location: importance in the prognosis of breast cancer patients and their correlation when breast cancer cells suffer stressful situations - Cuello Carrión, Fernando Darío (2015)
In human breast cancer, β-catenin localization has been related with disease prognosis. Since HER2-positive patients are an important subgroup, and that in breast cancer cells a direct interaction of β-catenin/HER2 has been reported, in the present study we have explored whether β-catenin location is related with the disease survival. The study was performed in a tumor bank from patients (n = 140) that did not receive specific anti-HER2 therapy. The proteins were detected by immunohistochemistry in serial sections, 47 (33.5 %) patients were HER2-positive with a long follow-up. HER2-positive patients that displayed β-catenin at the plasma membrane (completely surrounding the tumour cells) showed a significant better disease-free survival and overall survival than the patients showing the protein on other locations. Then we explored the dynamics of the co-expression of β-catenin and HER2 in human MCF-7 and SKBR3 cells exposed to different stressful situations. In untreated conditions MCF-7 and SKBR3 cells showed very different β-catenin localization. In MCF-7 cells, cadmium administration caused a striking change in β-catenin localization driving it from plasma membrane to cytoplasmic and perinuclear areas and HER2 showed a similar localization patterns. The changes induced by cadmium were compared with heat shock, H2O2 and tamoxifen treatments. In conclusion, this study shows the dynamical associations of HER2 and β-catenin and their changes in subcellular localizations driven by stressful situations. In addition, we report for the first time the correlation between plasma membrane associated β-catenin in HER2-positive breast cancer and survival outcome, and the importance of the protein localization in breast cancer samples.